x+5
---------------
-x^2-7x-10
x+5
---------------
-(x+5)(x+2)
-1
---------------
(x+2)
2007-06-20 18:59:00
·
answer #1
·
answered by sweet n simple 5
·
0⤊
0⤋
Answers with Solutions
Qns. 1:
= ( x + 5 ) / -x² -7x -10
= ( x + 5 ) / ( x + 5 )( -x - 2 )
= 1 / ( -x - 2 )
Hope This Solutions Will Help In Answering Your Questions ;)
G0n9 G0n9â¢
Mathematician
2007-06-21 03:40:32
·
answer #2
·
answered by Kelvin 2
·
0⤊
0⤋
= - (x + 5) / (x² + 7x + 10)
= - (x + 5) / (x + 5).(x + 2)
= - 1 / (x + 2)
2007-06-21 02:37:55
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
Whenever you are asked his type of question, they are essentially asking you to factor the denominator.
In this case, as the numerator is x+5 it is probably a good bet that x+5 is one of the factors in the denominator.
As you can see,
-x^2-7x-10 => -(x^2+7x+10) => -(x+5)(x+2) it is!
Therefore, looking at the whole equation.....
x+5
___________
-(x+5)(x+2)
Now you can simplify, since (x+5)/(x+5) = 1, your answer will be:
-1
__
(x+2)
2007-06-21 01:59:19
·
answer #4
·
answered by sharky.mark 4
·
0⤊
1⤋
Ans is :
-x^2 - 7x - 10 = -(x^2 + 7x + 10) = -(x+2)(x+5)
So,
(x+5) / ( - (x+2) (x+5) ) = - 1/ ( x+2) QED
2007-06-21 02:03:51
·
answer #5
·
answered by Maxis 2
·
0⤊
0⤋
consider the denominator
-x^2-7x-10
= -(x^2+7x+10)
= -(x^2+2x+5x+10)
= -[x(x+2) + 5(x+2)]
= -(x+2)(x+5)
now,
x+5
---------------
-x^2-7x-10
=-(x+5)/(x+2)(x+5)
on cancelling x+5 ,
=-1/(x+2)
2007-06-21 02:07:47
·
answer #6
·
answered by may_5 2
·
0⤊
0⤋
take a negative 1 out of the bottom then factor it. (x+5)(x+2) then cross out the (x+5) s and you are stuck with -1 over (x+2)
2007-06-21 02:06:58
·
answer #7
·
answered by ♥Summer♥ 2
·
0⤊
0⤋
x+5
---------------
-(x^2+7x+10)
x+5
---------------
-(x+5)(x+2)
= -1/(x+2)
2007-06-21 02:01:36
·
answer #8
·
answered by PaeKm 3
·
0⤊
0⤋
Limit.
2007-06-21 02:02:07
·
answer #9
·
answered by Tuncay U 6
·
0⤊
0⤋
1
______
-(x-2)
2007-06-21 02:02:41
·
answer #10
·
answered by Midor1 1
·
0⤊
0⤋